Autoimmunity and lymphoproliferation markers in naïve HCV-RNA positive patients without clinical evidences of autoimmune/lymphoproliferative disorders. Issue 8 (August 2016) - Gulli, Francesca; Basile, Umberto; Gragnani, Laura; Fognani, Elisa; Napodano, Cecilia; Colacicco, Luigi; Miele, Luca; De Matthaeis, Nicoletta; Cattani, Paola; Zignego, Anna Linda; Rapaccini, Gian Ludovico
Abstract: Background: HCV can lead to both chronic liver disease and B-cell lymphoproliferative disorders. A strong association exists between HCV and mixed cryoglobulinaemia (MC). Methods: Anti-nuclear antibodies (ANA), rheumatoid factor Ig-G (RF-IgG), free light chain κ and λ (FLC-κ, FLC-λ) levels and κ/λ ratio were evaluated in 50/420 subjects unexpectedly resulted anti-HCV positive after routine screenings for non-hepathological procedures. Results: Three/fifty patients had HCV-RNA undetectable in the serum and were excluded from the analysis. Thirty-nine/fifty patients had laboratory evidence of circulating cryoglobulins without liver disease and MC-related symptoms. Among them, 17 resulted ANA-positive. The mean cryocrit was higher in ANA-positive patients, while no other demographic/clinical differences were observed between the groups. Significantly higher levels of RF-IgG were observed in ANA-positive vs ANA-negative patients. κ and λ FLC were higher in ANA-positive patients. A ROC analysis, based on ANA-positivity vs ANA-negativity, confirmed a high sensitivity and specificity of RF-IgG test. Conclusions: Published data concerning MC come mostly from symptomatic vasculitis. We analyzed HCV-patients without MC symptoms, founding cryoglobulins in the majority of them. The increased levels of FR-IgG and FLC in CGs-ANA-positive patients, suggest these test could be used to identify a state of silent autoimmune and/or lymphoproliferative condition before the transition to a frank disease in naïve HCV-patients without symptoms of extrahepatic manifestations.